2014
DOI: 10.1108/ijdrbe-02-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

Re-framing planning decision-making: increasing flood resilience in Jakarta

Abstract: Purpose – The purpose of this paper is to re-frame planning decision-making to address risks of flooding and to increase community resilience. Rapid urbanisation, fragmented governance and recurrent flooding complicate resolution of DKI Jakarta’s chronic housing shortage. Failure to effectively implement planning decision-making processes poses potential human rights violations. Contemporary planning policy requires the relocation of households living in floodplains within 15 m of DKI Jakarta’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…It has been found that a lack of interaction and communication between related key actors seems to be one of the main causes of this coordination issue [107]. As described by prior studies, another possible reason is the policy and institutional fragmentation within the arena of flood risk management in Jakarta [124,125].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that a lack of interaction and communication between related key actors seems to be one of the main causes of this coordination issue [107]. As described by prior studies, another possible reason is the policy and institutional fragmentation within the arena of flood risk management in Jakarta [124,125].…”
Section: Resultsmentioning
confidence: 99%
“… (1) (Allan et al, ; Coaffee, , ; Fitzgerald & Laufer, ; Johnson & Blackburn, ; Malalgoda et al, ; Wilby & Keenan, ); (2) (Bakker & Morinville, ; Cigler, ; Danar & Pushpalal, ; Dias et al, ; Ernstson, , ; Pierdet, ; Schewenius, McPhearson, & Elmqvist, ); (3) (Cousins, ; Ernstson, , ; Ernstson et al, ; Fitzgerald & Laufer, ; Smith et al, ; Wagenaar & Wilkinson, ); (4) (Berke & Campanella, ; Coaffee, , ; Crichton, ; Fitzgerald & Laufer, ; Sharma & Singh, ); (5) (Bosher et al, , ; Cigler, ; Friend et al, ; Sunarharum et al, ); (6) (Galaz, ; Gupta, ); (7) (Galaz, ); (8) (Brown et al, ; Kelman, ; Meerow & Newell, ; Zaidi & Pelling, ); (9) (Hill, ; McPhearson et al, ); (10) (Gupta, ; Horney et al, ); (11) (Kehinde, ; Liu et al, ); (12) (Haigh & Sutton, ; Kapucu, ; Stewart, Kolluru, & Smith, ); (13) (Liu et al, ); (14) (Roberts, ; Sellberg et al, ; Zaidi & Pelling, ); (15) (Gotham, ; Haigh and Amaratunga, ); (16) (Horney et al, ; Liu et al, ); (17) (Horney et al, ; Kapucu, ; Storsjö & Kachali, ); (18) (Kehinde, ); (19) (Berke & Campanella, ; Liu et al, …”
Section: Resultsmentioning
confidence: 99%
“…In some industries, inherent conflicts arise around the design of an infrastructure: while a levee might be crucial for risk reduction, it may have been built to primarily serve the shipping industry (Cigler, ). During implementation, a lack of information on risks and poor information transmission to concerned parties can also impede resilience initiatives (Friend et al, ; Sunarharum, Sloan, & Susilawati, ). Moreover, past infrastructure decisions can be a major impeding factor as they are difficult to undo and shape views about current options (Gupta, ).…”
Section: Resultsmentioning
confidence: 99%
“…Much of the literature on resilience and policy responses to flooding in Jakarta focuses on relative vulnerability to flooding, conducting comparison at the city scale (or large suburban scale) of physical exposure, governance institutions or demographic characteristics (e.g. Akmalah and Griggs, 2011; Caljouw et al., 2005; Dickson et al., 2012; Firman et al., 2011; Renald et al., 2016; Sunarharum et al., 2014). These studies have found the physically vulnerable areas in the city, such as North Jakarta, and demonstrated the multiplying effects of subsidence and climate change on flooding.…”
Section: Reorienting Urban Resiliencementioning
confidence: 99%